2020
DOI: 10.1016/j.ijid.2020.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Onset of valganciclovir resistance in two infants with congenital cytomegalovirus infection

Abstract: Ganciclovir and its prodrug valganciclovir are elective treatments for cCMV. Neonates with important symptoms undergo 6 months of therapy to ameliorate/prevent symptoms and late sequelae, but evidence of resistance is emerging. Over the last 5 years, we took care of 59 cCMV infants and experienced two cases of resistance among nine cCMV infants receiving long-term valganciclovir therapy. In the first case, valganciclovir therapy was prolonged beyond 6 months due to severity of symptoms, control of viral load, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…In contrast with short‐term, long‐term side effects are poorly known and may cause concern. Animal models showed impaired fertility and carcinogenic toxicity but similar findings have not been found in humans 5,37,39–44 . Today, it is generally only recommended to treat children with moderately to severely symptomatic cCMV because their symptom severity exceeds the risk for side effects 10 .…”
Section: Discussionmentioning
confidence: 62%
“…In contrast with short‐term, long‐term side effects are poorly known and may cause concern. Animal models showed impaired fertility and carcinogenic toxicity but similar findings have not been found in humans 5,37,39–44 . Today, it is generally only recommended to treat children with moderately to severely symptomatic cCMV because their symptom severity exceeds the risk for side effects 10 .…”
Section: Discussionmentioning
confidence: 62%
“…A treatment period longer than 3 months appears to be a risk factor for antiviral drug resistance [ 30 ] in immunocompromised patients. Recently, antiviral drug resistance has been reported in patients with cCMV infection [ 8 , 31 35 ]. It was observed that GCV resistance emerged after 3 months in patients with cCMV infection [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, antiviral drug resistance has been reported in patients with cCMV infection [ 8 , 31 35 ]. It was observed that GCV resistance emerged after 3 months in patients with cCMV infection [ 8 ]. A 6-month GCV/VGCV treatment is the recommendation for cCMV therapy [ 6 ]; therefore, careful CMV blood load monitoring is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim is to prevent the onset of deafness or to prevent it from getting worse, in cases where it is already present. Although this is the recommended therapy, cases of resistance to treatment (approximately 4%) are also reported [6,21]. Studies to determine the effectiveness of valganciclovir in infected but asymptomatic or isolated deaf newborns are ongoing (NCT03301415, NCT03107871, NCT01649869) [22,23,24], and a study evaluating the pharmacokinetics of letermovir in the treatment program is scheduled for 2022 [1,6].…”
Section: Postnatal Treatment Of CMV Infectionmentioning
confidence: 99%